It was mean to happen explaining cultural variations in fate attributions. [article]. - Norenzayan, Ara
People often perceive important and improbable life outcomes as "meant to happen", that is, predetermined and inevitable. In 4 studies, we constructed diverse measures of such fate attributions and examined the cultural correlates of this attributional tendency, focusing on ethnic culture and religious affiliation differences. Independently of ethnic culture, Christians were found to endorse fate attributions more than did the nonreligious, and independently of religious affiliation, East Asian Canadians attributed events to fate more than did European Canadians. Consistent with theoretical predictions, the religious affiliation difference was mediated by belief in God, whereas the ethnic cultural difference was mediated by a measure of causal complexity, although not by a measure of acculturation. It was mean to happen : explaining cultural variations in fate attributions.Experimentally inducing thoughts of causal complexity in one domain increased fate attributions in unrelated domains. These results point to 2 independent psychological sources of fate attributions which also explain observed cultural differences in this tendency.
Keywords: Attribution; Fate; Culture; Belief; Religion